The The Mark Usage as Message Nuances in Digital Chat Communication Between Japanese and Indonesian Written Communication - Dharma, Hendy Reginald Cuaca; Sandjojo, Cecilia A; Kariko, Abdul A T (PT FORMOSA CENDEKIA GLOBAL, 2023)
Exclamation mark or kantanfu in Japanese, is one of written language elements used to convey expressions. Based on exclamation mark usage, the meaning and nuance of a sentence could differ. Amidst the COVID19 pandemic that limits one’s interaction to another, the frequency of digital communication has significantly increased. Digital communication through chats has become an activity that cannot be separated from everyday life. Therefore, it is important to understand exclamation marks correctly. The aim of this study is to avoid misunderstandings that could happen through chats in Japanese. This study will compare the use and interpretation of exclamation marks in Japanese chat between Indonesians and Japanese. Japanese chat messages containing exclamation marks were analyzed using Hymes’ SPEAKING theory. This study uses Creswell's convergent mixed methods, with quantitative data of Indonesians’ questionnaire survey results, and qualitative data of interviews with Japanese people. Study results show that there are differences in the use and function of exclamation marks between Indonesians and Japanese.